De Djawatan City Forest Management Strategy As A Tourist Attraction In Benculuk Village, Banyuwangi Regency - Angga Dana Saputra; Yayu Indrawati; Sri Widowati (International Journal of Technology and Education Research, 2025)
The complexity of managing tourist attractions becomes problematic when the tourist destination is also a conservation area. Conservation areas are currently often important locations for tourism activities. In conditions like this, urban forests are very much needed to improve the quality of the city's environment. This research is important to do because of the need for proper management efforts. Then, an in-depth evaluation is needed regarding effective and sustainable strategies in the De Djawatan city forest. In addition, by understanding external and internal factors, policies can be designed that can be implemented. This research was conducted with the aim of producing an appropriate tourism management strategy in the De Djawatan city forest as a benchmark in managing tourism as a future tourist attraction. By analyzing current management conditions, then analyzing internal and external factors that influence tourism management. After that, a tourism management strategy is developed using qualitative methods and data analysis using IFAS, EFAS, and SWOT analysis. This is inseparable from the potential of De Djawatan to become a sustainable tourist attraction in order to have a positive impact on tourism stakeholders, local governments, and the surrounding community.